THE INVESTIGATION OF GENE POLYMORPHISM β2 - ADRENOCEPTORS IN CHILDREN WITH BRONCHIAL ASTHMA - Banadyha, N. V.; Voloshyn, S. B. (Journal of Education, Health and Sport, 2015)
Banadyha N. V., Voloshyn S. B. The investigation of gene polymorphism β2 - adrenoceptors in children with bronchial asthma. Journal of Education, Health and Sport. 2015;5(12):417-423. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35565 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A417-423 http://pbn.nauka.gov.pl/works/683080 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 17.12.2015. THE INVESTIGATION OF GENE POLYMORPHISM β2 - ADRENOCEPTORS IN CHILDREN WITH BRONCHIAL ASTHMA N. V. Banadyha, S. B. Voloshyn Department of Pediatrics of Education-Research Instituteof Postgraduate training of the I.Ya. Horbachevsky Ternopil State Medical University, Ternopil, Ukraine Abstract Given the importance of genetic factors in causing bronchial asthma (BA), should be noted that according to some researchers it stands on the importance of the role of adverse environmental factors and a lifestyle. Genetic factors contribute to human health by 40%, in the case of BA - in 60% of cases it is due to hereditary. Objective: to analyze the frequency of polymorphic loci associations rs 1042713 (Arg16Gly) of ADRβ2 gene in children with BA. Materials and Methods. In-depth clinical examination using the special methods of investigation, conducted to 62 children suffering from BA, older than 5 years. The results of investigation. As a result of depth collection of anamnesis, it was revealed that in 73,68% of patients the anamnesis was unburdened. Mostly the family inheritance depends on mother health (57,14%), regardless of the severity of BA. Іt was found that in both types of inheritance (paternal and maternal) dominated genotype Arg16Gly (respectively: 58,33% and 60,00%). However, genotype Arg16Arg was observed in individual patients and in the case of intermittent disease. In case of allergen-induced and virus-induced phenotypes the genotype Arg16Gly (respectively: 44,70%; 58,30%) was more often diagnosed. Among the examined patients, BA manifested at the early age in 18 children (33,96%) in preschool age in 17 children (32,08%), and in a primary school in 18 children (33,96%). The early debut of disease associated with genotype Arg16Gly manifested at the early age in 66,67% of children and in preschool age – in 58,82%, while late manifestation observed in children with genotype Gly16Gly. It was clarified that intermittent flow associated with two genotypes: Arg16Gly (47,37%) and Gly16Gly (42,11%) The persistent mild course of BA replied to genotype Gly16Gly (64,71%), but with moderate persistent - to Arg16Gly (57,69%). Found that girls often associated with asthma genotype Gly16Gly (56,52%) and Arg16Gly (39,13%) while the boys with genotype Arg16Gly (53,84%), less with Gly16Gly (38,89%). Conclusions. When treating the patient, the established differences in allele polymorphisms gene ADRβ2, regarding the age and gender, should be taken into account. Keywords: children, bronchial asthma, β2 – adrenoceptors, polymorphism of the gene.